2021
DOI: 10.1111/aos.15082
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biomicroscopy of the anterior segment in patients with primary congenital glaucoma: a review of the literature

Abstract: Purpose.Primary congenital glaucoma (PCG) is a form of childhood glaucoma caused by maldevelopment of the anterior chamber. Disease severity differs greatly amongst patients. Ultrasound biomicroscopy (UBM) is a non-invasive technique that can visualize the anterior segment in infants in vivo. The purpose of this narrative review is to make an overview of the UBM data in PCG and study the applicability of UBM in characterizing the disease. Methods. AnonlinesearchwasperformedonPubMedinDecember2020.Afteracritical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Contact UBM delivers images with resolutions near to immersion UBM with advantage of sterility for patients with recent operations [4] . This study agreed with Abdolrazaghnejad A et al, [5] who found that B Scan ultrasonography is relatively contraindicated in the presence of rupture globe to avoid further trauma and contamination of the wound, so primary closure should be performed previous to ultrasound examination [2] . If ultrasound examination has to be performed prior to primary closure, it should be performed with caution to prevent possible trauma to the eye.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Contact UBM delivers images with resolutions near to immersion UBM with advantage of sterility for patients with recent operations [4] . This study agreed with Abdolrazaghnejad A et al, [5] who found that B Scan ultrasonography is relatively contraindicated in the presence of rupture globe to avoid further trauma and contamination of the wound, so primary closure should be performed previous to ultrasound examination [2] . If ultrasound examination has to be performed prior to primary closure, it should be performed with caution to prevent possible trauma to the eye.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrasound Biomicroscopy (UBM) is a technique used for imaging of the ocular anterior segment. It was first introduced by Pavlin and Foster in the early 1990's to obtain crosssections of the ocular tissues at microscopic resolution [2] . Compared to regular ultrasound modalities such as B scan which uses a frequency (10 MHz), UBM uses a much higher frequency transducer (35-100 MHz) [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The type A angle morphology of ARS in our study shared similarities with the ultrasound biomicroscopic features reported in primary congenital glaucoma (PCG), which also arises from the hindered posterior sliding of uveal tissue. These shared features include a thin iris, small ciliary body, abnormal tissue membrane, anterior iris insertion, and absence of Schlemm’s canal ( 30 , 31 ), thus constituting evidence supporting the phenotypic overlap between ARS and PCG.…”
Section: Discussionmentioning
confidence: 99%
“…UBM can be used to measure any quadrant on living subjects, as it is unaffected by shrinkage. Since its inception, UBM has been used in many clinical and preclinical studies associated with CB-related disease, and it is irreplaceable for the study of the posterior chamber and the innermost structures of the iridociliary region compared to AS-OCT [4,[18][19][20]. To the best of our knowledge, this is the first report that demonstrated the morphology parameters of the CB from both radial and transverse scans in four different quadrants in vivo of Chinese people and the correlations between them with systemic and ocular parameters.…”
Section: Discussionmentioning
confidence: 99%